Three-Level Car Security System with GPS Tracker Using IoT - Zulkifli, Nurin Azwin; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2023)
Nowadays, car theft is common and because of that, there is a need to invest on a car security system. Hence, this work focusses on developing a Three-level car security system with GPS Tracker using IoT. Arduino Mega 2560 module act as a microcontroller for RC522 RFID module and R307 fingerprint scanner module which is for the first and second level security. A 4×3 matrix keypad and NEO-6M GPS are integrated with the NodeMCU ESP8266 Wi-Fi module for the security and GPS tracking system. The car security system consists of three level security which are RFID tag, fingerprint scanner and keypad password. Upon entering the car, the owner has to tag the RFID before scanning the fingerprint and entering the password. The owner is given three chances to enter the password or else, the GPS tracking is activated. In worst case scenario, the thief might enter the car by force and steal the car. In this case, the owner shall receive a notification via text message on Blynk application and email for second notification. Furthermore, the location of the car can also be obtained from the NEO-6M GPS tracking system which is linked to the Blynk application on the owner’s mobile phone. The Blynk application shall display the location of the car on Google maps together with its latitude and longitude. It is shown from this work that the car security system provides a sufficient level of security to avoid car theft. In addition, the GPS tracking system is able to detect the location of the car which is displayed on the Blynk application installed in car owner’s mobile phone.